Edukasi Pemanfaatan Sisa Makanan Untuk Menjadi Produk Bernilai Ekonomi - Ririh Dian Pratiwi; Hayu Wikan Kinasih; Retno Indah Hernawati (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
Banana is a fruit that is easy to get and relatively cheap, so it is widely consumed by the public. The fiber and potassium content are very good for health. However, bananas have the disadvantage of ripening quickly. Therefore, it is necessary to provide education and training so that housewives can use these bananas into products that are useful and have economic value. The aim of this education and training is expected to be a source of inspiration for housewives to be more creative in utilizing household leftovers and be economically independent.